A Low Temperature And Pressure Methanol Synthesis - Muhammad Arif bin Zainal, Muhammad Arif (Universiti Teknologi Petronas, 2009)
Researchers and industrial practitioners have been discussed a lot about methanol synthesis nowadays. This is because due to the high demand of methanol itself in processing formaldehyde, chloromethanes, amines, acetic acid, MTBE and methyl methacrylate. In addition of that, currently methanol synthesis using syngas has attracted this researchers and industrial practitioner since it involving greenhouse gas which is CO2. Methanol synthesis reaction is an exothermic reaction. Researchers are still trying to find a way to lower down the operating conditions (e. g temperature and pressure) because of controlling the temperature inside the reactor is difficult. Besides, high operating conditions may deactivate the catalyst, thus lowering down the CO conversion, yield and not less may lowering down the selectivity of methanol. Since that sulphur free synthesis gas has been able to produce, Cu-based catalyst, a more active catalyst can be used and a low pressure and temperature methanol synthesis is more feasible. The study on low temperature methanol synthesis using 2-butanol has been successful and currently been applied in big scale. However, there is still no well-establish study on low temperature and pressure using aromatics solvent as catalytic solvent, thus gain the author interest to study on this matter. In the first semester, the author come out with some theory about how methanol is produced after done some deep research. The project continued in the second semester with catalyst preparing, catalyst characterization, run methanol synthesis reaction in a three phase reactor and samples analysis. In this project, two aromatics solvents (toluene and xylene) is use in the process of synthesizing methanol at temperature of 150 - 200°C and pressure of 20 bar. Percentage of total carbon conversion and yield will be observed as well as the selectivity at the end of this project